Toxoplasmosis in Patients with Cardiac Disorders: a Systematic Review and Meta-Analysis - Khazaei, Sasan; Asadi, Negar; Majidiani, Hamidreza; Foroutan, Masoud; Khalkhali, Hamidreza; Hazrati-Tappeh, Khosrow; Khademvatan, Kamal; Yousefi, Elham; Khademvatan, Shahram (Novelty in Biomedicine, 2022)
Toxoplasmosis is a common and serious infection caused by an obligatory intracellular protozoan, Toxoplasma gondii. This study investigated the possible association between heart failure and toxoplasmosis. We searched for toxoplasmosis and heart failure patients in English databases including PubMed, Scopus, ISI Web of Sciences, Science Direct, EMBASE, and Google Scholar up to June 2018. A total of 6 studies and 1,795 participants, comprising 934 cases and 861 controls, had acceptable criteria for entering the study. Immunoglobulin G (IgG) antibodies against T. gondii were found in 53% (22 to 83) of patients with heart diseases and 26% (11 to 42) of healthy controls. In comparison, immunoglobulin M (IgM) antibodies were found in 0.5% (0.1 to 1) in patients with heart diseases and 0.3% (0 to 0.7) of healthy controls. The patients suffering from cardiac disorders were more significantly correlated to anti-T. gondii IgG (OR: 3.53; 95% CI, 2.27 to 5.47; P = 0.014) and IgM (OR: 1.80; 95% CI, 0.31 to 10.4; P = 0.028) seropositivity than healthy controls. Despite limitations such as the low number of studies, our research showed a high association between toxoplasmosis and cardiac disorders. Therefore, toxoplasmosis may be a risk factor in cardiac patients, and more studies are being done.